2019
DOI: 10.1002/iub.2020
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E: Regulatory role in the cardiovascular system

Abstract: Cardiovascular disease (CVD) is one of the major causes of morbidity and mortality, all around the world. Vitamin E is an important nutrient influencing key cellular and molecular mechanisms as well as gene expression regulation centrally involved in the prevention of CVD. Cell culture and animal studies have focused on the identification of vitamin E regulated signaling pathways and involvement on inflammation, lipid homeostasis, and atherosclerotic plaque stability. While some of these vitamin E functions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(68 citation statements)
references
References 120 publications
1
65
0
2
Order By: Relevance
“…The properties of vitamin E have been known for many decades. Many studies have analyzing the effects of vitamin E in cardiovascular diseases [21], immunity [22], treating and preventing osteoarthritis [23]. However, interest in tocotrienols has awakened due to their biological effects and the therapeutic properties [24,25].…”
Section: Tocopherols and Tocotrienolsmentioning
confidence: 99%
“…The properties of vitamin E have been known for many decades. Many studies have analyzing the effects of vitamin E in cardiovascular diseases [21], immunity [22], treating and preventing osteoarthritis [23]. However, interest in tocotrienols has awakened due to their biological effects and the therapeutic properties [24,25].…”
Section: Tocopherols and Tocotrienolsmentioning
confidence: 99%
“…B vitamins, in particular folic acid, cardiovascular diseases, may be linked to the improvement of endothelial function, associated with the increase of 5-methyltetrahydrofolate reductase with the reduction of the circulating homocysteine [58]. Vitamin E, instead could play a role in endothelial homeostasis in respect to local inflammation, lipid metabolism and the stability of atherosclerotic plaques [59].…”
Section: Discussionmentioning
confidence: 99%
“…In case of γ-tocopherol, Japanese mallotus contained the highest amount (295.36±0.44 mg/100 g) and Australian laurel contained the second highest, which is a relatively higher amount (156.30±3.51 mg/100 g) compared to the rest 8 seed oils. γ-tocopherol limits the pro-inflammatory cytokine release in the body and is therefore resistant against inflammatory responses (Sozen et al, 2019). Similar to β-tocopherol, δ-tocopherol is reported to exist trivial in plants and the result of present study also reflects this, showing the highest content in Australian laurel, 12.62±0.54 mg/100 g. Based on the result of this study, Australian laurel showed a relatively higher amount of 4 types tocopherols as well as total tocopherol compared to the other oils.…”
Section: Tocopherol Contentsmentioning
confidence: 99%